GAMBARAN KEBERSIHAN PERSONAL DENGAN PREVALENSI INFEKSI CESTODA USUS PADA PETUGAS KEBERSIHAN RUMAH POTONG HEWAN KRIAN - Acivrida Mega Charisma; Farida Anwari; Windy Puji Ashari (Jurnal Media Analis Kesehatan, 2022)
Intestinal Cestode infection is still one of the problems in Indonesia, because Indonesia is one of the largest tropical areas where the population is infected with Taeniasis and Sistercosis. In Indonesia, there are three provinces that are endemic to taeniasis / cysticercosis, namely North Sumatera, Bali and Papua. Taeniasis cases have also occurred in East Java, to be precise in the city of Surabaya. The total prevalence of intestinal cestodes was recorded to be still high, namely arpund 72%, in Enterobiasis 28%, Ascaris 4%, Hymenolepis 4%, and Taenia saginata 36%. The purpose of this study was to describe the personal hygiene of janitors with the prevalence of intestinal ther cestode infection at the Krian Slaughterhouse. This research a purposive sampling technique, the samples were taken from cow feces and cleaners ath the slaughterhouse. The analysis of this calculation uses the statistical calculation of the Chi-square model. The samples studied were 50 samples. Namely, 25 from cow feces and 25 from nail samples from cleaning workers in slaughterhouses. The personal hygiene was analyzed using a questionnaire and microscopic observation using a sample of cow feces and nails of cleaning workers. The result showed 15 (60%) Taenia saginata infection, Taenia solium 5(20%).